Biodiesel production in a semiarid environment: A life cycle assessment approach - Biswas, Wahidul; Barton, L.; Carter, D. (American Chemical Society, 2011)
While the use of biodiesel appears to be a promising alternative to petroleum fuel, the replacement of fossil fuel by biofuel may not bring about the intended climate cooling because of the increased soil N2O emissions due to N-fertilizer applications. Using a life cycle assessment approach, we assessed the influence of soil nitrous oxide (N2O) emissions on the life cycle global warming potential of the production and combustion of biodiesel from canola oil produced in a semiarid climate. Utilizing locally measured soil N2O emissions, rather than the Intergovernmental Panel on Climate Change (IPCC) default values, decreased greenhouse gas (GHG) emissions from the production and combustion of 1 GJ biodiesel from 63 to 37 carbon dioxide equivalents (CO2-e)/GJ. GHG were 1.1 to 2.1 times lower than those from petroleum or petroleum-based diesel depending on which soil N2O emission factors were included in the analysis. The advantages of utilizing biodiesel rapidly declined when blended with petroleum diesel. Mitigation strategies that decrease emissions from the production and application of N fertilizers may further decrease the life cycle GHG emissions in the production and combustion of biodiesel.